P431 A Pan-European Real-World Study of SB5 biosimilar following transition from reference adalimumab: The PROPER study; 48-week analysis of persistence. (30th January 2023) - Dignass, A; Gisbert, J P; Bossa, F; Kelly, O; Rahman, M; Lobatón, T; Addison, J
Abstract: Background: SB5, a biosimilar to reference adalimumab (ADL) received marketing authorisation in 2017 (EU) and 2019 (US) based on pre-clinical and clinical phase I and III study data demonstrating bioequivalence and comparable efficacy, safety and immunogenicity to ADL. The real-world study "Pan-EU Real-World Experience with Imraldi" (PROPER) was designed to provide insights into outcomes, including predictors of persistence, following transition from ADL to SB5 outside the randomised, controlled trial setting. Methods: Under an umbrella design, 1040 patients with immune-mediated inflammatory disease (rheumatoid arthritis [RA], axial spondyloarthritis [axSpA], psoriatic arthritis [PsA], Crohn's disease [CD] or ulcerative colitis [UC]) who had received at least 16 weeks of treatment with ADL prior to transition to SB5 were enrolled at centres in Belgium, Germany, Ireland, Italy, Spain and the UK and followed for 48 weeks post-transition. Candidate predictors of persistence on SB5 included sex, medical history, age, duration of disease, disease score and concomitant therapy, all as recorded at time of SB5 initiation. Variables of clinical relevance reported for at least 15% of each cohort were selected as candidate predictors and fitted into a univariate Cox regression model. Persistence on SB5, i.e., time to SB5 discontinuation up to Week 48 post-transition was estimated using the Kaplan-Meier method. This abstract presents results for the CD cohort. Results: Of 447 CD patients included, 433 completed 48 weeks' follow-up; 316 of those (70.7%) remained on SB5 throughout. The probability of persistence (95% Confidence Interval [CI]) at Week 48 was 71.8% (67%, 76%) (Figure 1). Figure 1. Persistence on SB5 Table 1 shows the six variables qualifying as candidate predictors in the CD cohort and the probability of each to predict persistence at Week 48. Being female was the only variable shown to be associated with non-persistence of SB5: Hazard ratio (95% CI) 2.21 (1.54, 3.18). The 95% CIs of the other variables all crossed 1.0. Table 1. Probability of candidate variable to predict persistence on SB5 Conclusion: The majority of the CD cohort remained on SB5 at 48 weeks after transition from reference ADL. Of the candidate predictors of persistence, only female sex was found to have an association with increased risk for SB5 discontinuation. A limitation of this finding is the low proportion of subjects discontinuing SB5 prior to Week 48, hence a low incidence of potential candidate predictors. When anticipating persistence, results suggest no evidence to mitigate against transition, within the baseline categories explored.